The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2006
DOI: 10.1002/pssb.200672559
|View full text |Cite
|
Sign up to set email alerts
|

Crystal stability and pressure‐induced phase transitions in scheelite AWO4 (A = Ca, Sr, Ba, Pb, Eu) binary oxides. I: A review of recent ab initio calculations, ADXRD, XANES, and Raman studies

Abstract: The structural properties of CaWO 4 , SrWO 4 , BaWO 4 , PbWO 4 , and EuWO 4 scintillating crystals under pressure have been studied by X-ray powder diffraction, X-ray absorption near-edge structure measurements, Raman spectroscopy, and ab initio density functional theory calculations. The results obtained from these studies will be reviewed here and their differences and similitudes discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(11 citation statements)
references
References 28 publications
0
11
0
Order By: Relevance
“…15, I2 / a, Z =4͒. [32][33][34][35] The barite ͑BaSO 4 type, SG no. 62, Pnma, Z =4͒ structure has also been included in our study because it has been observed in CaSO 4 ͑Ref.…”
Section: Ab Initio Resultsmentioning
confidence: 99%
“…15, I2 / a, Z =4͒. [32][33][34][35] The barite ͑BaSO 4 type, SG no. 62, Pnma, Z =4͒ structure has also been included in our study because it has been observed in CaSO 4 ͑Ref.…”
Section: Ab Initio Resultsmentioning
confidence: 99%
“…fergusonite (I2/a) ? P2 1 /n, with the different phase-transition pressures being dependent on the sensibility of different techniques (Manjon et al 2006;Lopez-Solano et al 2007;Errandonea and Manjon 2008). For raspite (PbWO 4 -II), a thermal-driven raspite to scheelite-structured transition was identified at 538°C by an in situ transmission electron microscopy observation (Wang et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The scheelite structure of ABX 4 compound can be described as consisting of BX 4 tetrahedral units and the A cations have eightfold oxygen coordination. 16 only from structural measurements. 1,11 Some of these postscheelite transitions have been found to be associated with a soft mode.…”
Section: Introductionmentioning
confidence: 99%